The Role of Service Quality and Location in Increasing Customer Loyalty with Customer Satisfaction as an Intervening Variable - Shoalihin, Shoalihin; Suhaety, Yeye; Lestari, Atun (International Journal of Science, Technology & Management, 2024)
This research aims to determine the effect of service quality and location on customer loyalty with customer satisfaction as an intervening variable for customers of the "Warung Pojok" restaurant. This research uses a purposive sampling technique through a questionnaire as data collection material with 100 respondents. In this research, service quality and location act as independent variables, while customer loyalty is the dependent variable with customer satisfaction as the mediating variable. This research uses quantitative methods and data analysis is carried out using statistical tests with the help of SPSS 21. The results of the research show that service quality and location have a positive effect on customer satisfaction. Furthermore, the variables of service quality and location also have a positive effect on customer loyalty. Apart from that, customer satisfaction has been proven to influence customer loyalty at the "WARUNG POJOK" restaurant. This indicates that good service quality and strategic business locations play an important role in providing consumer satisfaction so that they can form loyal customers.